2014
DOI: 10.5539/ies.v7n2p18
|View full text |Cite
|
Sign up to set email alerts
|

Educational Encouragement, Parenting Styles, Gender and Ethnicity as Predictors of Academic Achievement among Special Education Students

Abstract: Current study examines the predictors' of academic achievement: role of parenting styles, educational encouragement, gender and ethnicity among special education students. Participants of this study consisted 200 special education students (N = 105 boys and N = 95 girls) age varies 14 to 19 years from one school located at Kuala Lumpur, Malaysia. Results showed authoritative parenting styles were mostly used by the parents of their special education students. Significant relationships were existed in parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…However, there is no depth research has been done on the effectiveness of this program in educating parents the importance of their involvement in child learning in and outside of school. Past researchers found that parental involvement helps in increasing student academic achievement and positive behaviors (Jeynes, 2007;Toldston, 2008;Plunkett et al, 2008;Kordi &Baharudin, 2010), student less aggressive and decreasing in dropout rates (Kratochwill et al, 2004), student become competent (Hill et al, 2004) and student more motivated (Khan et al, 2014).…”
Section: Problem Statementmentioning
confidence: 99%
“…However, there is no depth research has been done on the effectiveness of this program in educating parents the importance of their involvement in child learning in and outside of school. Past researchers found that parental involvement helps in increasing student academic achievement and positive behaviors (Jeynes, 2007;Toldston, 2008;Plunkett et al, 2008;Kordi &Baharudin, 2010), student less aggressive and decreasing in dropout rates (Kratochwill et al, 2004), student become competent (Hill et al, 2004) and student more motivated (Khan et al, 2014).…”
Section: Problem Statementmentioning
confidence: 99%
“…Artinya, meskipun dukungan informasional yang diberikan orang tua masih rendah, akan tetapi dukungan ini memiliki hubungan yang bermakna besar dengan pencapaian prestasi akademik anak. Hubungan antara dukungan informasional orang tua dengan prestasi akademik ini sejalan dengan penelitian Khan et al (2014) yang menyatakan dukungan orang tua yang diberikan kepada anak akan memengaruhi motivasi anak untuk meningkatkan prestasinya dan melanjutkan pendidikan. Dukungan ini berperan penting sebagai faktor protektif yaitu faktor yang melindungi, meringankan, menyangga, dan dengan demikian mengurangi resiko yang dialami individu sehingga individu terbantu melakukan penyesuaian sosial yang adaptif.…”
Section: Pembahasanunclassified
“…Past studies highlighted that parental involvement facilitates schools in producing excellent students (Hoover-Dempsey and Sandler, 1997; Fan and Chen, 2001; Jeynes, 2011; Ismail and Abdullah, 2013) by preventing disciplinary problems (Bear et al , 2014; Ahmad et al , 2017) and reducing the dropout rate (Kratochwill et al , 2004). In addition, Hill and Tyson (2009) highlighted that students are also more competent and motivated (Khan et al , 2014). In conclusion, the encouragement and support from parents in school activities are advantageous to students.…”
Section: Introductionmentioning
confidence: 99%